Palmitoylation-driven immune dysregulation and prognostic signature in low-grade glioma: a multi-omics and functional validation study - Zehao Wang; Tianlun Yu; Yuqiao Liu; Yufan Wu; Jingqing Hu; Jingqing Hu (Frontiers in Pharmacology)
BackgroundPalmitoylation, a critical post-translational modification, regulates protein localization and function in cancer. However, its role in glioma progression, immune modulation, and prognosis remains poorly understood.MethodsWe integrated transcriptomic, clinical, and mutation data from multicenter cohorts to analyze 30 palmitoylation-related genes in low-grade gliomas (LGG). Consensus clustering, differential expression analysis, and LASSO regression were employed to define palmitoylation clusters, identify prognostic genes, and construct a risk signature. The evaluation of immune infiltration and immunotherapy efficacy was further conducted across different risk groups. In the palmitoylation-related risk model, IGFBP2 was functionally validated through siRNA-mediated knockdown and a series of assays, including EdU incorporation, cell cycle analysis, wound healing, and transwell migration assays.ResultsTwo palmitoylation clusters (A/B) were identified, with Cluster B exhibiting poorer survival (P < 0.001), enriched JAK-STAT signaling, and elevated immune infiltration (M1/M2 macrophages, CD8+ T cells). A five-gene prognostic signature (CHI3L1, IGFBP2, MEOX2, EMILIN3, SFRP2) demonstrated robust predictive accuracy in training (AUC 0.92–0.94) and validation cohorts (AUC 0.68–0.83). High-risk patients showed upregulated PD-1, PD-L1, and CTLA4 (P < 0.001) and higher TIDE scores, indicative of immune dysfunction. IGFBP2 knockdown suppressed glioma cell proliferation (P < 0.01) and migration (P < 0.001), linking it to tumor aggressiveness.ConclusionPalmitoylation plays a pivotal role in LGG progression by influencing immune evasion and stromal interactions. The developed prognostic signature and nomogram offer practical tools for risk stratification in clinical settings, with IGFBP2 identified as a promising therapeutic target. These insights highlight the potential of palmitoylation-focused therapies to enhance outcomes for LGG patients.